2006
DOI: 10.1002/chin.200619237
|View full text |Cite
|
Sign up to set email alerts
|

Organic Chemistry in Water

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 1 publication
1
51
0
1
Order By: Relevance
“…As a result, the IL immobilized catalyst is regenerated and can be used for further reactions. Water is known to be the cheapest, environmentally benign, safe and most abundant compound on the earth's surface; and it has attracted a great deal of attention from a green chemistry perspective [33][34][35][36][37][38][39][40][41][42][43]. In addition, water also holds some unique physical and chemical properties, such as high surface tension, hydrogen bonding capability, high dielectric constant and high cohesive energy density [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the IL immobilized catalyst is regenerated and can be used for further reactions. Water is known to be the cheapest, environmentally benign, safe and most abundant compound on the earth's surface; and it has attracted a great deal of attention from a green chemistry perspective [33][34][35][36][37][38][39][40][41][42][43]. In addition, water also holds some unique physical and chemical properties, such as high surface tension, hydrogen bonding capability, high dielectric constant and high cohesive energy density [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The afore mentioned paper report a simple, cost-effective procedure to produce gold nanoparticles that are stable with extended shelf life. Recent reports have shown an increased use of water as solvent in chemical reactions instead of organic solvents [32]. The water dispersible nature of gold nanoparticles from grape byproducts along with its inherent health benefits can revolutionize the impact of nanotechnology on drug/nutraceutical delivery.…”
Section: Use Of Grape Waste Pineapple Anona and Other Citrusmentioning
confidence: 99%
“…Water as a solvent is not only inexpensive and environmentally benign but also provides completely different reactivity (Li & Chen, 2006). It has been suggested that the effect of water on organic reactions may be due to the high internal pressure exerted by a water solution, which results from the high cohesive energy of water (Breslow, 1991).…”
Section: Knoevenagel Reactions In Watermentioning
confidence: 99%